Analysis contribution hotel tax, restaurant tax and entertainment tax as srouce local revenue Bogor City - Sukarno, Aji; Haryono, Haryono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
So many efforts made by the Indonesian government to build the State of Indonesia into a developed country. One way is to do a lot of infrastructure development such as building transportation access and improving the quality of public facilities. Funds needed to build transportation access and improve the quality of public facilities can be obtained from various sources. One of them through local taxes. Bogor City Regional Tax consists of hotel tax, restaurant tax, entertainment tax and others. This research has a purpose to know the contribution of hotel tax, restaurant tax and entertainment tax as source of Original Regional Income of Bogor City in 2012 until 2016. The type of data used is secondary data. Data collection techniques used were interviews and documentaries. The results of this study indicate that the contribution of hotel tax is very small as a source of income Original Regional Bogor City. Restaurant tax has a small contribution as a source of Revenue Original Region of Bogor City. And the contribution of entertainment tax in the city of Bogor is also very small.